663 Regulations and enforcement in off-highway vehicle parks is associated with safer riding behaviours. (1st September 2016) - Jennissen, Charles; Waters, Jessica; Denning, Gerene; Robinson, Emily; Baranow, Eilis; Johnson, Brandon; Johnson, Nathaniel; Wetjen, Kristel; Hoogerwerf, Pam; Harland, Karisa
Abstract : Background: Previous studies showed that Iowa all-terrain vehicle (ATV) crash victims from off-highway vehicle (OHV) parks practiced safer riding behaviours than off-road crash victims outside the parks. The objective of this study was to determine the effect of regulations and enforcement on the prevalence of safety behaviours among Iowa OHV park users. Methods: From May to September of 2014, motion-activated cameras captured photos of users at the entrances of Iowa's eight OHV parks. Riders were coded by vehicle type, estimated age, sex, and safety behaviours. Descriptive and multivariable logistic regression analyses were performed. Results: A total of 6, 718 vehicles and 9, 083 riders were analysed. Among OHV park users, 44% were on ATVs, 51% on dirt bikes and 5% on side-by-sides (SxSs). Helmet use was 94% overall. Just 6% of single-rider ATVs and 0.8% of dirt bikes had passengers. While only 11% of park users on ATVs were <16 years old, 59% of the child operators were driving adult sized ATVs. Of those riding SxSs, 64% were not using their restraints. As compared to young adult (16–39 years) ATV riders, children were 6 times more likely to wear a helmet and adults 40–60 years old were half as likely. When officers were patrolling the parks, there was a 3.6-fold higher likelihood of helmet use and a 40% lower likelihood of passengers on dirt bikes and ATVs. Conclusions: Regulated safety behaviours (helmet use and riding without passengers) were highly common among OHV park users. However, unregulated behaviours (SxS restraint use and children driving youth-sized ATVs only) had lower compliance. Moreover, regulated safety behaviours were significantly increased when the parks were patrolled. This study shows that a combination of regulation and enforcement is effective in ensuring safety behaviour compliance in OHV parks. Similar efforts outside parks could have a substantial effect on decreasing off-road vehicle-related deaths and injuries.